Tajikistan : First and Second Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Performance Criteria, and Request for Augmentation of the Arrangement; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Tajikistan. (IMF Staff Country Reports; Country Report ;, 2010)
Tajikistan was hit by severe external shocks in 2009. The government plans to address the structural energy deficit and achieve energy independence. Tajikistan should proceed with care on the Roghun project, paying close attention to social, macroeconomic, and debt sustainability. The need is to strike a careful balance between social and capital spending, which are complementary for growth. Macroeconomic policies are appropriate, but the weakened health of the banking sector and of state-owned enterprises needs to be addressed urgently.